The causal relationship between trade openness and economic growth of Algeria in the period 1990-2018 using causality Toda Yamamoto (TYDL) - Bendjelloul, Khaled; Hamza, Baali; Benkhalifa, Ahmed (Dirassat Journal Economic Issue, 2021)
The study aimed to test the long-term causal relationship between trade openness and economic growth using the TYDL methodology for the case of Algeria during the period 1990-2018, and to achieve this goal annual data were obtained for both the open trade (Open) variable and the economic growth variable (Cro), and by following Methodological steps (TYDL), which mainly depend on the test of the WALD of the enlarged (MWALD). The study found that there is a causal relationship in one direction only from the trade openness towards economic growth and the absence of the causal relationship in the opposite direction. On the other hand, the study concluded that the economic growth of Algeria does not it benefits greatly from trade openness in light of the unitary export.